Réflexions sur l’ordinateur et l’assurance contre le vol, la fraude, l’espionnage industriel ou commercial - Dalpé, Jean (Assurances)

(untitled) (HEC Montréal, 1981)
The computer processing system is indeed an extraordinary tool but one which, in the hands of very clever but dishonest individuals, may quite easily be appropriated for personal gain. Although coverage is currently available in the form of crime insurance, the author points out in the text below that ordinary theft, fidelity and burglary insurance is not sufficient to caver the specific needs of the specialized data processing firms. Mr. Dalpé cites more comprehensive insurance coverage which is reviewed by Mr. André Towner in an analysis of a policy designed expressly for electronic data processing and media equipment risks.